2021
DOI: 10.1021/acs.est.1c03749
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Predicting the Size-Dependent Inhalation Intake of Particulate Novel Brominated Flame Retardants

Abstract: The risk of human exposure to particulate novel brominated flame retardants (NBFRs) in the atmosphere has received increasing attention from scientists and the public, but currently, there is no reliable approach to predict the intake of these compounds on the basis of their size distribution. Here, we develop a reliable approach to predict the size-dependent inhalation intake of particulate NBFRs, based on the gas/particle (G/P) partitioning behavior of the NBFRs. We analyzed the concentrations of eight NBFRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…Organic matter (OM), an important component of reactive substances in particles, plays a key role during the processes of adsorption, partitioning, and complexation of organic pollutants. 8,11 As shown in Figure S1, the OM fractions (f om ) in TSP ranged from 8.9 to 28.8% (mean of 18.8%), which was consistent with previous results in Izmir, Turkey (mean of 23.3%). 26 Furthermore, the data showed a significant exponential decrease in f OM with the increasing particle size (R 2 = 0.99, p < 0.05).…”
Section: Impact Of Om On Size-dependent Distribution Of Pfas In Parti...supporting
confidence: 91%
See 1 more Smart Citation
“…Organic matter (OM), an important component of reactive substances in particles, plays a key role during the processes of adsorption, partitioning, and complexation of organic pollutants. 8,11 As shown in Figure S1, the OM fractions (f om ) in TSP ranged from 8.9 to 28.8% (mean of 18.8%), which was consistent with previous results in Izmir, Turkey (mean of 23.3%). 26 Furthermore, the data showed a significant exponential decrease in f OM with the increasing particle size (R 2 = 0.99, p < 0.05).…”
Section: Impact Of Om On Size-dependent Distribution Of Pfas In Parti...supporting
confidence: 91%
“…The dynamic exchange of organic pollutants between the gas and particle phases is an important process that ultimately affects their environmental fate . Size-dependent distribution and gas-particle partitioning have been commonly used to describe the distribution behavior of organic pollutants such as polycyclic aromatic hydrocarbons (PAHs), organophosphate flame retardants (OPFRs), and novel brominated flame retardants (NBFRs) between the gas and particle phases. Comparatively, few studies on atmospheric PFAS have been documented. Lin et al found that perfluoroalkyl carboxylic acids (PFCAs) tended to distribute in fine particles, whereas perfluoroalkyl sulfonic acids (PFSAs) were dominantly affiliated in coarser particles.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, as an important parameter to describe the diffusion-partitioning behavior of LCMs between LL and LGP, the partition fraction for LCM i in LGP part (ϕ LGP‑ i ) was defined using eq by referring to the gas/particle partitioning models. ,, Since the concentrations of LCMs in LL were much higher than those in LGP (Table S6), C LGP‑ i in the denominator was ignored, and this equation was further rewritten as follows: Ø LGP i = normalC LGP i / ( C LL i + C LGP i ) normalC LGP i / normalC LL i …”
Section: Methodsmentioning
confidence: 99%
“…Diffusion-Partitioning Model Development. An approach of the gas/particle partitioning process of SVOC including parameters of the predicted subcooled vapor pressures (P L ) and K oa 11,28,31 to model the diffusionpartitioning process of LCMs from LL to LGP and SP was conducted. The evaluation of equilibrium partitioning of organic compounds between two phases is commonly performed using double logarithmic correlations.…”
Section: Sample Preparation and Instrument Analysismentioning
confidence: 99%
“…In recent years, Harbin, a megacity in Northeast China, has experienced severe and continuous haze conditions in winter, which has had serious impacts on the social economy, ecological environment, and human health [29,30] . The temperature in Harbin can range from below -30 °C in winter to > 35 °C in summer, so Harbin provides an ideal research area to study how the weather and air quality influence human exposure to atmospheric BFRs.…”
Section: Introductionmentioning
confidence: 99%